PROJECT TEAMS AND THEIR ROLE AND PLACE IN GOVERNMENT ORGANIZATIONS (American Journal of Business Management, Economics and Banking, 2025)
This article explores the role and significance of project teams in government organizations, focusing on their contributions to achieving organizational goals, fostering innovation, and improving service delivery. Through an examination of existing literature, methodological analysis, and case studies, this study highlights best practices, challenges, and strategies for optimizing project team performance in the public sector.